Penerapan Pendekatan Komunikatif dalam Menulis Persuasif Kelas VII SMPN 1 Bone - Indramini Indramini (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
The purpose of this study was to determine the communicative approach in writing persuasive texts for class VII of SMPN 1 Bone. This research method uses a classroom action research method. Student learning outcomes in cycle I data of class VIII students of SMPN 53 Makassar by giving a test to make persuasive texts and giving scores. With a total overall score of 4,635 students with two test tests. The first test test with an average value of 70.72 for the average value of the second test test 74.13 the total average of the overall test test is 72.42 which is in the low category. After getting the test scores of all students in cycle I, it was continued in cycle II. Meanwhile, cycle II of class VIII students of SMPN 53 Makassar by giving a test to make persuasive texts and giving scores. With a total overall score of 5,410 students with two test tests. The first test test with an average value of 82.47 for the average value of the second test test 86.59 overall from the test test, namely 84.53 in the good category. Based on the test results in cycles 1 and 2, it can be seen that implementing a communicative approach can improve the learning outcomes of class VIII students of SMPN 53 Makassar. This is indicated by an increase in the initial score on the average content aspect in cycle I of 72.42 and in cycle II the score became 84.53.